Ireland and sub-Saharan Africa, 1955-75 : a changing mission - O'Sullivan, Kevin (Trinity College (Dublin, Ireland). Department of History, 2008)
This thesis uses the example of sub-Saharan as a framework through which to analyse the evolution of Irish foreign policy between 1955 and 1975. It was a period of considerable change. When Ireland joined the United Nations in 1955 it ended a period of international isolation and allowed the Irish government to re-engage with international affairs and to re-state and re-defme the principles that governed its attitude to foreign policy. In the five years that followed its independent approach, particularly visible in its attitude to the decolonisation process, won it a considerable amount of support from across the political spectrum, and led later analysts to define the period as a kind of ‘golden age’ in Irish foreign policy. What followed through the emergence of a vocal and increasingly radical group of newly-independent Afro- Asian states served to temper Irish enthusiasm. The involvement of Irish troops in the United Nations peacekeeping force in the Congo between 1960 and 1964 brought about a maturity in the state’s attitudes to international affairs. The deaths of Irish troops brought home the very real sacrifices to be made in the pursuit of Ireland’s principles, and the detrimental effect of the Congo crisis on the United Nations highlighted the limitations to Ireland’s commitment to that organisation in the pursuit of international peace and stability.
Keywords: Modern History, Ph.D.; Ph.D. Trinity College Dublin